Fenomena Quiet Quitting pada Tenaga Kesehatan dalam Konteks Lingkungan Kerja dan Motivasi Intrinsik: Scoping Review - Adistya Nugraha F.; Herin Mawarti; Nasrudin Wangi; Ade Armada Sutedja (Universitas Muhammadiyah Manado, 2025)
Hospitals are currently facing a serious challenge with the phenomenon of quiet quitting, in which employees perform only minimal tasks without active engagement in their work. This situation has the potential to lower the quality standards of healthcare services and increase the risks of burnout and turnover. The aim of this scoping review is to map work environment factors, the role of intrinsic motivation, and indicators of quiet quitting among healthcare professionals. The method applied in this review followed the Arksey and O’Malley framework and adhered to PRISMA-ScR guidelines. Relevant articles were searched in PubMed, Scopus, and ProQuest databases using specific keywords, screened based on inclusion and exclusion criteria, and analyzed narratively. The results showed that out of 772 identified articles, only 7 met the eligibility criteria and were included for review. The findings revealed that excessive workload, lack of organizational support, weak leadership, role ambiguity, and negative organizational culture are dominant work environment factors consistently linked to quiet quitting. Psychosocial aspects such as burnout and poor work–life balance further reinforce this tendency. On the other hand, intrinsic motivation particularly meaning at work, autonomy, a sense of relatedness, and opportunities for growth emerged as protective elements that can reduce the risk of minimal engagement. Indicators of quiet quitting include low involvement, lack of initiative, limited communication, and performing only tasks stated in formal contracts. The discussion highlights that this phenomenon negatively affects patient care quality, decreases job satisfaction, and increases turnover intention. Therefore, healthcare organizations need to create a supportive work environment, strengthen intrinsic motivation, and provide managerial interventions that promote psychological well-being and autonomy at work as preventive strategies.